The Expressions of CD30 and CD123 of Mastocytosis in Taiwan. Issue 4 (6th April 2022) - Yang, Ching-Fen; Hsu, Chih-Yi
Abstract : Mastocytosis is a rare disease with a low incidence in Asia-Pacific populations. CD30 and CD123 may have potential prognostic and therapeutic value, but the results are inconsistent. Because racial disparities may exist, we aim to evaluate the expressions of CD30 and CD123 in a series of mastocytosis cases in Taiwan. Twelve patients with systemic and 7 with cutaneous forms of mastocytosis were studied. The expressions of CD30 and CD123 were correlated with the clinical features of the patients. Eighty-three percent (10/12) of patients with systemic mastocytosis (SM) had an associated hematological neoplasm. Four of the SM patients had both "B" and "C" findings, and they had a median survival time of 0.9 months. CD30 expression was positive in 50% (6/12) of SM cases and 100% (6/6) of cutaneous mastocytosis cases. CD123 was expressed focally or weakly in only 2 SM-associated hematological neoplasm cases. The distribution of mastocytosis subtypes and the expression of CD30 and CD123 in Taiwan differed from those reported in North America and Europe. However, mastocytosis, especially indolent forms, is easily overlooked as its heterogeneous and nonspecific clinical manifestations. A high index of suspicion and improved diagnostic methods can be helpful.